TOX: lezioni di tossicologia - Dolara, Piero (Electronica, 2006)
TOX is a manual aimed primarily at the Toxicology courses of the Faculty of Pharmacy and Science, that can also be profitably utilised by students following different degree courses in other Faculties (Medicine, Agriculture, Engineering)and by anyone else looking for a thorough but succinct overview of toxicological questions. TOX covers the principal sectors of general toxicology (acute and chronic toxicity, mutagenesis, teratogenesis, carcinogenesis, reproductive toxicity, oxidative damage, epidemiological methods), specialist toxicology(dietary toxicity, tobacco smoke, pesticides, N-nitroso compounds, heterocyclic amines and aromatic amines toxicity) and environmental toxicology (environmental estrogens, PAH, heavy metals, dioxins and polychlorinated di-benzo-furans, water and air pollution).